(untitled) (Swiss Medical Weekly, 2020)
AIM To assess neonatal transport activities by the neonatal transport teams of the University Children’s Hospital Zurich in order to identify opportunities for improvement in the organisation of these transports. METHODS Retrospective analysis of prospectively collected data on neonatal transports by the neonatal transport teams of the University Children’s Hospital Zurich between January 2014 and December 2018. Data on transports affecting neonates with a corrected gestational age of up to 44 weeks and a weight less than 5 kg were extracted from registration forms, transport forms, transport reports and the neonates’ medical charts. Transport data were assessed separately for urgent, non-urgent and re-transfers. RESULTS During the study period, 1110 transport runs, including 883 (79.5%) urgent, 105 (9.5%) non-urgent and 122 (11.0%) re-transfers were performed. Ground transport accounted for 90.7% of the cases. The majority (77.7%) of the transported neonates were born at term and 59.1% were transported within the first 24 hours of life. The most common reason for transport was respiratory distress (39.9%), followed by cardiac diseases (14.6%). Medical procedures performed by the neonatal transport teams during transport mostly addressed peripheral intravenous line placement (41.8%) and feeding tube placement (41.8%). The median preparation time for urgent transfers was 35 min (range 8–225) for ground and 50 min (range 20–260) for air transport. CONCLUSIONS The high proportion of urgent transfers emphasises the need for an efficient neonatal transport system and dedicated neonatal transport teams staffed by members with training in neonatal transport and expertise in handling neonatal emergencies. To provide the best possible care to the vulnerable neonates, the heterogeneous nature of the cohort of transported neonates regarding the diagnoses transport demand was made for and the medical procedures performed during transport should be considered in simulation training of neonatal transport team staff. Additionally, processes to improve preparation time should be defined and implemented in order to reduce it to less than 30 min so as to guarantee efficient care. Further studies are needed to assess the quality and efficacy of neonatal transports in Switzerland. National guidelines on the standard of neonatal transport and quality metrics should be established in order to set benchmarks and to improve the quality of the transports.